2017
DOI: 10.1007/s00704-017-2163-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations of aridity indices in Iraq

Abstract: This study investigates the spatial and temporal variations of the aridity indices to reveal the desertification vulnerability of Iraq region. Relying on temperature and precipitation data taken from 28 meteorological stations for 31 years, the study aims to determine (1) dry land types and their delineating boundaries and (2) temporal change in aridity conditions in Iraq. Lang's aridity (Im), De Martonne's aridity (Am), United Nations Environmental Program (UNEP) aridity (AIu), and Erinç aridity (I E) indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…Tabari, Hosseinzadeh Talaee [26] also reported a rising trend in aridity in most parts of Iran during 1966-2005. Pour, Abd Wahab [2] reported a significant shift of 4.84% semi-arid land to arid land in Iran between 1951-1980and 1987 reported a shift of semi-arid region to higher aridity in Turkey during 1991-2006 compared to 1960-1990.Şarlak and Agha [27] reported increasing aridity in recent years in the predominantly arid country of Iraq. In recent years an increasing tendency in aridity is also reported in Iraq [27].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Tabari, Hosseinzadeh Talaee [26] also reported a rising trend in aridity in most parts of Iran during 1966-2005. Pour, Abd Wahab [2] reported a significant shift of 4.84% semi-arid land to arid land in Iran between 1951-1980and 1987 reported a shift of semi-arid region to higher aridity in Turkey during 1991-2006 compared to 1960-1990.Şarlak and Agha [27] reported increasing aridity in recent years in the predominantly arid country of Iraq. In recent years an increasing tendency in aridity is also reported in Iraq [27].…”
Section: Discussionmentioning
confidence: 98%
“…However, studies related to changes in aridity are still very limited in the region. Few studies on aridity trends have been conducted in some regions like Iran [24][25][26], Iraq [27], Turkey [28], Lebanon [29,30] and Egypt [31]. But such studies are still lacking in the majority of the regions, particularly for conflict-affected countries.…”
Section: Introductionmentioning
confidence: 99%
“…Drought is a natural disaster that could be occurred in all regions with different climate conditions. Drought can be affected on the surface water resources, underground water resources, agriculture water demand, water consumption in natural resources, industry, humans and wildlife sections [6,10,21,26,28,36,37,40,43]. Drought develops slowly, is difficult to detect and can present a range of diverse aspects in different regions [1,39].…”
Section: Introductionmentioning
confidence: 99%
“…Al-Faraj et al (2015) explored drought and analyzed indicated climate changeinduced alterations in transboundary Diyala watershed presenting a generic technical template to support decision-makers for management in transboundary watersheds (Al-Faraj, Scholz, Tigkas, & Boni, 2015). Şarlak and Mahmood Agha (2017) showed that arid and semi-arid regions cover about 97% of the country areas (Iraq) and it was observed that the aridity index tend to decrease for all stations used in the study. (Şarlak & Mahmood Agha, 2017).…”
Section: Introductionmentioning
confidence: 99%